Incidencia de brucelosis bovina (Brucella abortus) en el cantón Pichincha, Provincia de Manabí - Vera Ganchozo, Ruben Dario (2013)
The carried out investigation had for object to determine the prevalence of bovine Brucellosis in the Canton Pichincha, County of Manabí, by means of the tests of Rose of Flare and confirmation with the reaction test in chain of the polymerase (PCR). The study was developed in the Canton Pichincha, County of Manabí, during the months of January to March of the 2013. For the investigation, they took samples of 5cc of blood for mature individual, obtaining a bovine total of 300 samples of animals of the Creole races and mestizos. The animals used in the investigation were selected in the properties that were previously assigned for the sampling of the animals; and, in each property he/she took the samples according to the number of assigned samples. The sample of blood was extracted of the vein half coccyges, 5 ml/animal was extracted. The blood was allowed to rest then for some minutes he/she took the serum. In laboratory, the method of quick agglutination was used with antigen of Brucella in Rosa of Flare and confirmation with the test (PCR). With this test it was detected the infected animals. The positive cases were evaluated by means of the Non Parametric Test for a single sample. Of a total of 300 samples gathered in 20 clusters of the canton Pichincha county of Manabí, 234 negative bovine units are had to brucellosis and 66 bovine units reacted positive to brucellosis what produces a total of 28, 21 prevalence%. The loss caused by this illness is of $532,50 for animal Key Words: Bovine, Brucella, Rosa of Flare